Geology, fluid inclusions, mineral and (S-O) isotope chemistry of the Badran orogenic Au deposit, Yana-Kolyma belt, eastern Siberia: implications for ore genesis - Fridovsky, Valery; Kryazhev, Sergey; Polufuntikova, Lena; Kudrin, Maxim; Anisimova, Galina (Frontiers in Earth Science, 2024)
The Badran orogenic gold deposit is located in the Yana-Kolyma belt, Eastern Siberia, it has proven reserves of ~ 9.3 t of gold and an average grade of 7.8 g/t. The total gold production at the Badran deposit since 1984 amounted to ~ 34 t. Despite many years of study, the origin of the gold deposits of the Yana-Kolyma metallogenic belt one of the world's largest belts, and the Badran deposit is controversial. Synthesis of regional geology and geology of the Badran deposit, fluid inclusion analysis, mineral and (S-O) isotope chemistry defines the genetic model, origin of fluids and source of metals in the evolution of the ore-forming system, equivalent to other orogenic gold deposits on the margin of the Siberian craton. The deposit is localized in the Upper Triassic clastic rocks and is controlled by the NW-trending thrust. Polyphase mineralization occurs as disseminated arsenian pyrite and arsenopyrite ores with invisible gold, quartz veins with native gold and Fe, Pb, Zn, Cu sulfides and sulfosalts of orogenic type, and locally post-ore Ag, Sb-bearing minerals and Hg epithermal features. The quartz veins with native gold were formed from a boiling low-medium saline (1.5–10 wt% NaCl eq.) aqueous-carbonic fluids at temperatures of 290 to 210 ºC and pressures of 300–250 to 125 bar. δ34S values of pyrite and arsenopyrite vary from –1.1‰ to +2.4‰, with an average of +0.4‰; the δ18О of quartz from +15.1‰ to +17.5‰ at constant δ18ОH2O about +7.5 ‰ (± 1.0‰). High contents of As (up to 2.4 wt%), Co/Ni ~ from 0.3 to 9.9 in pyrite of proximal alteration, are typical for hydrothermal systems. The results obtained confirm that the ore-forming fluids did not have a single origin, but were formed from a mixture of subcontinental lithospheric mantle and metamorphic sources. The subcrustal lithospheric mantle was fertilized in the time preceding mineralization (Late Jurassic) and was derived directly from the down-going subduction slab and overlying sediment wedge at the closure of the Oymyakon Ocean.